STRATEGY IMPROVING THE QUALITY OF PUBLIC SERVICE IN THE CAPITAL INVESTMENT AND SERVICE SERVICE INTEGRATED ONE DOOR OF THE BANJAR CITY WEST JAVA PROVINCE - Bustomi, Thomas; Harison, Soni; Alamsyah, Kamal (International Journal of Psychosocial Rehabilitation, 2020)
---There is still the view of the community that considers that the delivery of public services is still very slow and inefficient in responding to changes and does not adjust to changes in the development paradigm. The many complaints made by the public, especially the business community in receiving public services from the government bureaucracy, include: convoluted procedures, no clarity about the time to resolve the problem, and no clarity about how much the cost must be incurred, plus the poor quality of service.The method used in this study is a qualitative research method, while the type of approach in this research is descriptive analysis. Analysis of the data used is the analysis of data according to Miles and Hubberman with a qualitative approach.The results showed that the gap between the quality of public services and community expectations still occurred, therefore there must be improvements in service performance related to the elements of service procedures, cost certainty, staff certainty, and speed of service. In the service that is currently considered good by the community is able to encourage investment activities in the City of Banjar, because it is able to create services that are cheap, fast and transparent. Transparency in public services has increasedBased on the results of the study it can be concluded that the DPMPTSP of Banjar City must continue to improve the quality of service with high commitment, consistency, and legal certainty. Improving the quality of service needs to be accompanied by a simplification program of service procedures so as to increase the speed of service, create a conducive work environment, and strengthen institutions as providers of licensing service activities can run effectively and efficiently through strengthening information and communication technology.